Exploring the Social and Cognitive Factors Shaping the Acquisition of Science Concepts among Primary School Students in first and second languages - Adebusuyi, O. F.; Adeleye, A. O.; Jimoh, D. O.; Ayide, D. K.; Adedoyin, A. B. (Journal of Science Education Research, 2024)
This study investigates the intricate interplay of social and cognitive factors influencing the acquisition of science concepts among primary school pupils, with a focus on their first and second language. A survey research design was carried out across different primary schools in Ijebu Ode Government Area of Ogun State, during the third term of the 2022/2023 academic year. A sample size of 268 primary four pupils, 196 from eight private and seventy-two (72) from three public primary schools, were randomly selected through simple random sampling technique. A pilot survey was conducted by administering the research instruments to 46 male and 72 female randomly selected primary 4 pupils after which the instruments were subjected to analysis. The data collected were analyzed using a t-test and hierarchical regression analysis. Regression analysis showed that pupil motivation, teacher support, parent support, and school environment have a significant contribution to pupils' science performance test (SPT). The results revealed a significant correlation between pupil motivation, teacher support, parental involvement, and the school environment, collectively influencing pupils' science performance. The study emphasizes addressing language disparities, enhancing student motivation, fostering collaborative support from parents and teachers, and creating a conducive learning environment in primary schools to improve overall science education performance.